Immune predisposition drives susceptibility to pneumococcal pneumonia after mild influenza A virus infection in mice - Palani, Sunil; Uddin, Md Bashir; McKelvey, Michael; Shao, Shengjun; Sun, Keer (Frontiers in Immunology, 2023)
Introduction A frequent sequela of influenza A virus (IAV) infection is secondary bacterial pneumonia. Therefore, it is clinically important to understand the genetic predisposition to IAV and bacterial coinfection. Methods BALB/c and C57BL/6 (B6) mice were infected with high or low-pathogenic IAV and Streptococcus pneumoniae (SPn). The contribution of cellular and molecular immune factors to the resistance/susceptibility of BALB/c and B6 mice were dissected in nonlethal and lethal IAV/SPn coinfection models. Results Low-virulent IAV X31 (H3N2) rendered B6 mice extremely susceptible to SPn superinfection, while BALB/c mice remained unaffected. X31 infection alone barely induces IFN-γresponse in two strains of mice; however, SPn superinfection significantly enhances IFN-γ production in the susceptible B6 mice. As a result, IFN-γ signaling inhibits neutrophil recruitment and bacterial clearance, leading to lethal X31/SPn coinfection in B6 mice. Conversely, the diminished IFN-γ and competent neutrophil responses enable BALB/c mice highly resistant to X31/SPn coinfection. Discussion The results establish that type 1 immune predisposition plays a key role in lethal susceptibility of B6 mice to pneumococcal pneumonia after mild IAV infection.